1996
DOI: 10.1136/adc.75.5.448
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and behavioural characteristics of cri du chat syndrome.

Abstract: Developmental and behavioural characteristics were assessed in 27 children with cri du chat syndrome using the Society for the Study of Behavioural Phenotypes questionnaire, which gave information on prenatal and perinatal conditions, neurological problems, and developmental and behavioural difficulties. The findings suggest that the behavioural profile of children with cri du chat syndrome incorporates selfinjurious behaviour, repetitive movements, hypersensitivity to sound, clumsiness, and obsessive attachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 9 publications
3
74
1
6
Order By: Relevance
“…Individuals with CdCS have similar levels of intellectual disability, expressive and receptive communication to those identified in CdLS (Cornish & Munir, 1988;Cornish, Bramble, Munir & Pigram, 1999). In contrast to individuals with CdLS, nonverbal communication skills and social interaction skills are reported to be a relative strength in CdCS (Cornish & Pigram, 1996;Cornish, Munir & Bramble, 1998;Sarimski, 2002) although, as is the case in CdLS, speech is compromised. These shared general and specific characteristics, makes CdCS an appropriate contrast group for this study.…”
Section: Introductionmentioning
confidence: 92%
“…Individuals with CdCS have similar levels of intellectual disability, expressive and receptive communication to those identified in CdLS (Cornish & Munir, 1988;Cornish, Bramble, Munir & Pigram, 1999). In contrast to individuals with CdLS, nonverbal communication skills and social interaction skills are reported to be a relative strength in CdCS (Cornish & Pigram, 1996;Cornish, Munir & Bramble, 1998;Sarimski, 2002) although, as is the case in CdLS, speech is compromised. These shared general and specific characteristics, makes CdCS an appropriate contrast group for this study.…”
Section: Introductionmentioning
confidence: 92%
“…For example, the lick and flip and self hug behaviors described in Smith Magenis syndrome (Dykens, Finucane & Gayley, 1997;Dykens & Smith, 1998;Finucane et al, 1994;Smith & Gropman, 2001) and the attachment to objects in Cri du Chat syndrome (Cornish & Pigram, 1996). These highly specific behaviors are masked when a class level of description is employed, highlighting the need to describe behaviors at a finegrained level.…”
Section: Insert Table 1 About Herementioning
confidence: 99%
“…In both cases, no other groups scored highly on these items and no other highly prevalent behaviors were identified within these groups. These behaviors have previously been described within the literature (Cornish & Pigram, 1996;Dykens & Smith, 1998;Smith & Gropman, 2001) although systematic study of these behaviors using standardised assessments has not been conducted previously. The fine-grained approach to repetitive behavior employed in this study enabled identification of these behaviors.…”
Section: Association With Autism Spectrum Phenomenologymentioning
confidence: 99%
“…Importantly, Sarimski (2002) has demonstrated that in addition to using verbal and non-verbal communication to indicate their needs, individuals with CdCS engage in significantly more socially directed communication than individuals with Cornelia de Lange syndrome, performing at a level that is similar to individuals with Down syndrome. However, Cornish and Pigram (1996) report that only 7.4% of individuals use any formal signs, the majority (48.1%) use idiosyncratic gestures. …”
Section: Communicationmentioning
confidence: 99%
“…A further 36.9% had limited but useful single word vocabularies. According to Cornish and Pigram (1996) only 25.9% of 27 individuals with CdCS used speech to communicate their needs while 55% were able to communicate using non-verbal methods. Importantly, Sarimski (2002) has demonstrated that in addition to using verbal and non-verbal communication to indicate their needs, individuals with CdCS engage in significantly more socially directed communication than individuals with Cornelia de Lange syndrome, performing at a level that is similar to individuals with Down syndrome.…”
Section: Communicationmentioning
confidence: 99%